DEVELOPMENT OF MATHEMATICAL LEARNING TOOLS BASED ON PROBLEM-BASED LEARNING (PBL) MODELS OF SINE AND COSINE RULES TO FACILITATE MATHEMATICAL PROBLEM-SOLVING ABILITY STUDENTS OF CLASS X SMA/MA - Siti Juariah; Yenita Roza; Susda Heleni (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
This study aims to produce a mathematical learning device based on the Problem-Based Learning (PBL) model of the sine and cosine rules to facilitate mathematical problem-solving skills (KPMM) for class X SMA/MA students that meet the valid criteria for syllabus, lesson plans, worksheets and practical for student worksheets. The development model used by the researcher is a 4-D model (four-D. The 4-D model consists of 4 stages, namely the definition stage, the design stage, the development stage, and the dissemination stage). Based on the data from the validation results, the learning tools developed in the form of syllabus, lesson plans and mathematics worksheets use the Problem Based Learning model on the sine and cosine rule material to facilitate the mathematical problem-solving abilities of class X SMA / MA students meet the very valid category and very practical category. From the results of this study it can be concluded that the syllabus, lesson plans, and worksheets are feasible to use.